Implementation of the Project-Based Learning Model Assisted by Audiovisual Media in Writing Review Texts Skill of Fictional Works Learning - Isna Isna; Yulianti Rasyid; Nursaid; Dadi Satria (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the planning, implementation, and evaluation of the application of the Project Based Learning (PjBL) model assisted by audiovisual media in teaching students to write fictional review texts in Grade VIII of SMP Negeri 1 Sutera. This research employed a descriptive qualitative approach. The research data were obtained through observation, interviews, and documentation. Observations were conducted to examine the planning, implementation, and evaluation processes of learning activities. Interviews were carried out with an Indonesian language teacher and five students of class VIII.4 who participated in the learning process. Documentation consisted of an analysis of the teaching modules and learning tools used by the teacher. The results indicate that the learning planning was systematically prepared in accordance with the Merdeka Curriculum, including the development of teaching modules, selection of audiovisual media, design of project-based learning activities, and determination of assessment techniques. The implementation of learning using the PjBL model assisted by audiovisual media was conducted in four meetings and followed the prescribed learning syntax. Students were actively involved in observing audiovisual media, participating in group discussions, developing review text projects, and presenting their work. The evaluation of learning was carried out comprehensively through pretests, process and project assessments, presentations, reflections, and posttests. The evaluation results show an improvement in students’ ability to write review texts, as indicated by the higher average posttest score compared to the pretest score. Therefore, the application of the Project Based Learning model assisted by audiovisual media has a positive impact on students’ learning outcomes in writing fictional review texts.